USE OF THE MICROWAVE ENERGY FOR ALUMINUM WASTE FOAMING - LUCIAN PAUNESCU; MARIUS FLORIN DRAGOESCU; SORIN MIRCEA AXINTE; ANA CASANDRA SEBE (Journal of Engineering Studies and Research)
The paper presents an aluminum foam experimental technique using the microwave energy. The raw material was recycling aluminum waste processed by ecological melting and gas atomizing to obtain the fine powder required in the foaming process. The powder mixture was completed with dolomite as a foaming agent. The products had a fine and homogeneous porous structure (pore size between 0.4-0.9 mm). The density (1.17-1.19 g/cm3), the compressive strength (6.83-7.01 MPa) and the thermal conductivity (5.71-5.84 W/m·K) had values almost similar to the foams made by conventional methods.